Stromal Galectin-1 Promotes Colorectal Cancer Cancer-Initiating Cell Features and Disease Dissemination Through SOX9 and β-Catenin: Development of Niche-Based Biomarkers - Peng, Kai-Yen; Jiang, Shih-Sheng; Lee, Yu-Wei; Tsai, Fang-Yu; Chang, Chia-Chi; Chen, Li-Tzong; Yen, B. Linju (Frontiers in Oncology, 2021)
Over 90% of colorectal cancer (CRC) patients have mutations in the Wnt/β-catenin pathway, making development of biomarkers difficult based on this critical oncogenic pathway. Recent studies demonstrate that CRC tumor niche-stromal cells can activate β-catenin in cancer-initiating cells (CICs), leading to disease progression. We therefore sought to elucidate molecular interactions between stromal and CRC cells for development of prognostically relevant biomarkers. Assessment of CIC induction and β-catenin activation in CRC cells with two human fibroblast cell-conditioned medium (CM) was performed with subsequent mass spectrometry (MS) analysis to identify potential paracrine factors. In vitro assessment with the identified factor and in vivo validation using two mouse models of disease dissemination and metastasis was performed. Prediction of additional molecular players with Ingenuity pathway analysis was performed, with subsequent in vitro and translational validation using human CRC tissue microarray and multiple transcriptome databases for analysis. We found that fibroblast-CM significantly enhanced multiple CIC properties including sphere formation, β-catenin activation, and drug resistance in CRC cells. MS identified galectin-1 (Gal-1) to be the secreted factor and Gal-1 alone was sufficient to induce multiple CIC properties in vitro and disease progression in both mouse models. IPA predicted SOX9 to be involved in Gal-1/β-catenin interactions, which was validated in vitro, with Gal-1 and/or SOX9—particularly Gal-1high/SOX9high samples—significantly correlating with multiple aspects of clinical disease progression. Stromal-secreted Gal-1 promotes CIC-features and disease dissemination in CRC through SOX9 and β-catenin, with Gal-1 and SOX9 having strong clinical prognostic value.